2013
DOI: 10.1371/journal.pone.0071452
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Contextual Factors and Substance Characteristics on Perspectives toward Cognitive Enhancement

Abstract: Enhancing cognitive performance with substances–especially prescription drugs–is a fiercely debated topic among scholars and in the media. The empirical basis for these discussions is limited, given that the actual nature of factors that influence the acceptability of and willingness to use cognitive enhancement substances remains unclear. In an online factorial survey, contextual and substance-specific characteristics of substances that improve academic performance were varied experimentally and presented to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 76 publications
6
77
1
Order By: Relevance
“…Correspondingly, in survey research by Sattler et al (2013a) amongst 1852 respondents, a lower score on both willingness-to-use a PCE and moral acceptability of PCE substances was reported when judging an imaginary situation where no other students take this PCE substance, compared to situations in which half of the other students or all fellow students were taking the PCE substance. Possibly, they read the “no other student” situation as one where there is inequality in opportunity with them having, and other students not having, access and found this to be morally unacceptable.…”
Section: Fairnessmentioning
confidence: 91%
“…Correspondingly, in survey research by Sattler et al (2013a) amongst 1852 respondents, a lower score on both willingness-to-use a PCE and moral acceptability of PCE substances was reported when judging an imaginary situation where no other students take this PCE substance, compared to situations in which half of the other students or all fellow students were taking the PCE substance. Possibly, they read the “no other student” situation as one where there is inequality in opportunity with them having, and other students not having, access and found this to be morally unacceptable.…”
Section: Fairnessmentioning
confidence: 91%
“…[28,33], see the discussion section for limitations of this approach). We experimentally varied five characteristics (dimensions) of this drug (magnitude, probability of enhancement effect, severity, probability of side effects, and drug price), and three characteristics of the social environment (peer prevalence, social disapproval, and social suggestions; see Table  2).…”
Section: Methodsmentioning
confidence: 99%
“…However, work in ADHD populations, including several randomised control trials, indicates that the psychostimulants are associated with relatively mild side effects such as a dry mouth [20,21]and reduced appetite but also more serious effects of increased in heart rate and blood pressure [21][22][23][24]. Comparative studies have found, perhaps unsurprisingly, that users are less concerned about the safety of smart drugs than non-users [6,25], and perceptions of the severity of possible health risks have been inversely associated with willingness to use smart drugs [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%